Smart Hydroponic System Using IoT - Abu Bakar Shedek, Muhmmad Amirudin; Mohamed Ali, Riyaz Ahmad (Evolution in Electrical and Electronic Engineering, 2023)
Hydro agriculture (Hydroponics), aqua agriculture (Aquaponics), and aerobic agriculture (Aeroponics), in addition to substrate culture, are examples of soilless farming. One of these hydroponics systems is gaining popularity due to its effective management of resources and food output. This project used The Nutrient Film Technique (NFT). NFT is a kind of hydroponic system in which nutrient solutions flow continuously through the plant roots. This project's objectives are to produce high-quality Brassica Rapa (Pak Choi) hydroponic plants using NFT, to monitor temperature, acidity, water level, and Total Dissolve Solids (TDS) readings on hydroponic drainage, and to reduce labour costs and time spent caring for hydroponic crops. Various kinds of sensors, including pH, humidity, TDS, and water level sensors, were employed to build a smart hydroponic system using IoT in order to meet the goals. Experiment 1 aims to identify suitable parameters such as temperature, AB fertiliser concentration, electrical conductivity (PPM), and acidity (pH) of the water solution that will be used in the hydroponic system for growing white mustard plants in experiments 2 and 3. This information was obtained on the harvest date, which is 35 days following the date of the nursery. The average weight for sale in the supermarket for white mustard is 160g.  In the comparative results of the experiment, experiment 2 needed almost 28 days to reach the average weight to be sold while experiment 3 only needed 25 days.  However, on the 35th day, the weight of mustard in experiment 2 was heavier than in experiment 3. Users can determine whether they want to produce a faster result using the parameters in experiment 3 or a heavier crop yield using the parameters found in experiment 2. This project will also be able to help small farmers as well as large industrial farmers.